Cognitive of Pre-service Teachers in Designing STEM-based Learning Using CODE-PLAN Model - Isnaini, Muhammad; Farwati, Ratna; Metafisika, Kartika; Nasrudin, Dindin (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
STEM-based learning implementation plan aims to integrate aspects of natural science, technology, engineering, and mathematics in a holistic learning activity. In the educational context, pre-service teachers have an important role in developing effective learning implementation plans to achieve learning goals and facilitate the student learning process. This study aimed to explore the cognitive abilities of prospective teachers in designing STEM-based learning implementation plans using the CODE-Plan model. This research was conducted using qualitative research methods involving several pre-service chemistry teachers as participants. Pre-service chemistry teachers design lesson plans based on the CATUR STEM guidebook (how to organize STEM Learning). This guidebook is a product developed by researchers. Data was collected through interviews, observations and analysis of documents related to learning implementation plans that pre-service chemistry teachers had made. The cognitive abilities of pre-service chemistry teachers in designing STEM-based learning implementation plans are assessed through several indicators, including clarity in formulating objectives, accuracy of integration of context and content, accuracy of a series of STEM-based learning activities, and completeness of the assessment. The results of the research show that most pre-service chemistry teachers have been able to make plans for implementing STEM-based learning by adapting the methods in the CATUR STEM guidebook. Some of the pre-service chemistry teachers have been able to formulate learning objectives in accordance with the chemistry curriculum, design STEM-based learning activities that are oriented towards learning objectives, and plan evaluations. Various chemistry issues in everyday life are correlated with chemistry material and presented in STEM-based learning activity plans by pre-service chemistry teacher students. However, pre-service chemistry teacher students still need to improve in planning the total lesson hours needed for each meeting, and some of the chemical issues used in these learning activities are difficult to implement in the classroom